PERBEDAAN PENINGKATAN KADAR BILIRUBIN NEONATUS BERDASARKAN UMUR KEHAMILAN - Dewayani, Evita Ratih; Widyasih, Hesty Widyasih; Wahyuningsih, Heni Puji (Poltekkes Kemenkes Yogyakarta, 2015)
Icterus neonatorum caused early neonatal mortality for about 6%. One of the causal factors was that the liver of the premature baby had not functioned perfectly, thus the indirect bilirubin conjugation became direct conjugation which had not adequate yet. In Gunung Kidul Regency, DIY, the number of childbirth less than 37 weeks increased and followed by the increasing of icterus neonatorum at the same time. The objective of this study was too obscene the difference increased of bilirubin levels based on the gestational age during the parturition. The research method was analytical observation, with historical cohort design, using secondary data. The research was conducted in Wonosari Regional Hospital (RSUD Wonosari). The subject of the research is the early neonatal case (newborn 0-7 days). Purposive sampling technique was used to obtain 90 respondents divided into two groups namely the exposure group 45 respondents (early neonatal which was born <37 weeks of the gestational age) and the non-exposure group 45 respondents (early neonatal which was born ? 37 weeks of the gestational age). The result showed that 34 early neonatal (75,56%) which was born < 37 weeks of gestational age and 14 early neonatal (31,11%) which was born >37 weeks of gestational age experienced icterus neonatorum. Approximately the early neonatal bilirubin levels (day 0-7) from the two groups compared, there were no significant differences on the day 0 until day 2, the peak of bilirubin levels on early neonatal which was born>37weeks of the gestational age occurred on the day 3, therefore the peak of bilirubin levels on early neonatal which was born < 37 weeks of the gestational age occurred on the day 4. The significance point 0.02 (p.value <0.05), with RR 2.43 Cl 95%(1,52-3,86). The Conclusion is that there were different increasing of early neonatal bilirubin levels, based on the gestational age during the parturition, increased bilirubin levels were higher in early neonatal which was bom<37 weeks of the gestational age.